Influence of partner diversity on collaborative public R&D project outcomes: A study of application and commercialization of nanotechnologies in the Netherlands - Raesfeld, Ariane von; Geurts, Peter; Jansen, Mark; Boshuizen, Johannes; Luttge, Regina (Technovation, 2012)
Several studies have indicated the importance of public R&D in the transfer and commercialization of nanotechnology. So far, few have focused on university–industry interaction and collaboration performance. In this study, we investigate the impact of technological diversity and value chain complementarity of partners on public nanotechnology R&D projects' performance. We enriched a database on the commercial outcomes of technology research projects from the Dutch Technology Foundation STW. To test our hypotheses, we selected 169 nanotechnology research projects from the database, which started in a five-year period from 1998 until 2003. Project performance was measured five years after completion of the project. Technological diversity has a U-shaped effect on the projects' commercial performance. Findings show a strong positive impact of value chain complementarity of partners on both application development and commercial performance of the projects.. The framework introduced in this study allows an evaluation of the effects of technological diversity and value chain complementarity on application development and the commercial performance of public R&D projects.